Contextuality of Negative Confirmation in E-Commerce Sales and Purchase Agreements - Jamil, Nury Khoiril; Masitho, Nisa; Utari, Agustine Rossa Diah (Jurnal Penegakan Hukum dan Keadilan, 2024)
Transactions through digital platforms have become indispensable due to their diverse features. Nevertheless, based on the law of engagement, most e-commerce companies apply standard contracts in transactions. E-commerce typically safeguards consumer rights, including complaints, returns, and ratings. Consumer ratings, particularly in transactions of minimal economic value, do not influence the safeguarding of consumer rights. It is interesting to investigate whether a negative assessment or rating of goods receipt constitutes a default agreement or a reason for the cancellation of the agreement. This research aims to examine the implementation of pacta sunt servanda in sales and purchase agreements within e-commerce and to analyze its implications regarding negative confirmation in contractual relationships. The method used in this research was normative juridical with legislation and a conceptual approach. The results highlight that the principle of pacta sunt servanda in Indonesia is implemented strictly and cannot be intervened by anyone as long as it fulfills legal requirements and does not violate statutory regulations, satisfying legal certainty. The principle of pacta sunt servanda has binding status on the agreement entered into, carried out between sellers and consumers. Nevertheless, it is not based on the assessment given by consumers regarding dissatisfaction with transaction results, in which regulations do not guarantee complete legal protection for consumers for dissatisfaction with transactions through the features provided. Consequently, a substantive approach is needed in assessing agreements. Legal validity and legal certainty of contracts are also necessary, but the value of proportional justice is important.